Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Sure! Let's find the limit of the function [tex]\(\frac{3m^2 - 3}{m - 1}\)[/tex] as [tex]\( m \)[/tex] approaches 1.
1. Identify the function and the limit to be evaluated:
We need to evaluate:
[tex]\[ \lim_{m \to 1} \frac{3m^2 - 3}{m - 1} \][/tex]
2. Assess direct substitution:
Start by substituting [tex]\( m = 1 \)[/tex] directly into the function:
[tex]\[ \frac{3(1)^2 - 3}{1 - 1} = \frac{3 - 3}{0} = \frac{0}{0} \][/tex]
The result is an indeterminate form, [tex]\( \frac{0}{0} \)[/tex]. Therefore, we need to use algebraic manipulation to simplify the expression.
3. Factor the numerator, if possible:
Factor the numerator [tex]\( 3m^2 - 3 \)[/tex]:
[tex]\[ 3m^2 - 3 = 3(m^2 - 1) \][/tex]
Notice that [tex]\( m^2 - 1 \)[/tex] can be factored further as a difference of squares:
[tex]\[ m^2 - 1 = (m - 1)(m + 1) \][/tex]
Therefore:
[tex]\[ 3m^2 - 3 = 3(m - 1)(m + 1) \][/tex]
4. Simplify the overall expression:
Substitute the factored form back into the original function:
[tex]\[ \frac{3(m - 1)(m + 1)}{m - 1} \][/tex]
Now, if [tex]\( m \neq 1 \)[/tex], we can cancel the common factor of [tex]\( m - 1 \)[/tex]:
[tex]\[ \frac{3 \cancel{(m - 1)} (m + 1)}{\cancel{m - 1}} = 3(m + 1) \][/tex]
5. Evaluate the limit of the simplified expression as [tex]\( m \to 1 \)[/tex]:
Now, as [tex]\( m \)[/tex] approaches 1:
[tex]\[ \lim_{m \to 1} 3(m + 1) = 3(1 + 1) = 3 \cdot 2 = 6 \][/tex]
Therefore, the limit is:
[tex]\[ \lim_{m \to 1} \frac{3m^2 - 3}{m - 1} = 6 \][/tex]
So, the result is 6.
1. Identify the function and the limit to be evaluated:
We need to evaluate:
[tex]\[ \lim_{m \to 1} \frac{3m^2 - 3}{m - 1} \][/tex]
2. Assess direct substitution:
Start by substituting [tex]\( m = 1 \)[/tex] directly into the function:
[tex]\[ \frac{3(1)^2 - 3}{1 - 1} = \frac{3 - 3}{0} = \frac{0}{0} \][/tex]
The result is an indeterminate form, [tex]\( \frac{0}{0} \)[/tex]. Therefore, we need to use algebraic manipulation to simplify the expression.
3. Factor the numerator, if possible:
Factor the numerator [tex]\( 3m^2 - 3 \)[/tex]:
[tex]\[ 3m^2 - 3 = 3(m^2 - 1) \][/tex]
Notice that [tex]\( m^2 - 1 \)[/tex] can be factored further as a difference of squares:
[tex]\[ m^2 - 1 = (m - 1)(m + 1) \][/tex]
Therefore:
[tex]\[ 3m^2 - 3 = 3(m - 1)(m + 1) \][/tex]
4. Simplify the overall expression:
Substitute the factored form back into the original function:
[tex]\[ \frac{3(m - 1)(m + 1)}{m - 1} \][/tex]
Now, if [tex]\( m \neq 1 \)[/tex], we can cancel the common factor of [tex]\( m - 1 \)[/tex]:
[tex]\[ \frac{3 \cancel{(m - 1)} (m + 1)}{\cancel{m - 1}} = 3(m + 1) \][/tex]
5. Evaluate the limit of the simplified expression as [tex]\( m \to 1 \)[/tex]:
Now, as [tex]\( m \)[/tex] approaches 1:
[tex]\[ \lim_{m \to 1} 3(m + 1) = 3(1 + 1) = 3 \cdot 2 = 6 \][/tex]
Therefore, the limit is:
[tex]\[ \lim_{m \to 1} \frac{3m^2 - 3}{m - 1} = 6 \][/tex]
So, the result is 6.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.